A longitudinal study of the impact of the Sydney Olympics on real estate markets. Issue 1 (16th March 2015) - Lu, Qiang (Steven); Yang, Yupin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the impact of the Sydney 2000 Olympic Games on the residential real estate markets of the host city during the bidding, pre-Olympic and post-Olympic periods. Design/methodology/approach – This study uses a difference-in-differences model to analyze the transaction prices for all properties in New South Wales, Australia for the period from 1980 to 2007. Findings – The paper finds that the impact on real estate markets varies across different suburbs in the host city and over time. The real estate markets of host suburbs experience substantially higher growth during the bidding and pre-Olympic periods but not during the post-Olympic period. However, the property prices in non-host suburbs in the host city increase at a higher rate during the pre- and post-Olympic periods but not during the bidding period. Originality/value – This study offers insights into the long-term impact of the Olympic Games on host suburbs and non-host suburbs in the host city during different periods by analyzing a large longitudinal data set over a period of 27 years.